Socio-economic impacts of land use changes in Lojing Highlands, Kelantan - Zaki, Pakhriazad Hassan; Ismail, Mohd Hasmadi; Bawon, Paiman; Baharom, Nor Azmi (Human Resource Management Academic Research Society, 2023)
The growth trajectory necessitates modifying extensive land use patterns, mainly by converting forests for alternative purposes such as large-scale agricultural farms, eco-tourism ventures, oil palm plantations, plantation forests, and urban expansion. In recent years, there has been a notable rise in the demand for agricultural products and flower cultivation in Lojing Highlands, making it a significant contributor to the country's export market. This surge in demand has positioned Lojing Highlands as a prominent region for the production and sale of these commodities, second only to Cameron Highlands. The allocation of land concessions to private entities and government-affiliated corporations has exerted significant strain on the indigenous group. The Temiar populations residing in the Lojing Highlands, whose livelihoods are reliant on the forest, have encountered significant obstacles as a result of alterations in land utilisation. The results of the study show that there was a land use change in the study area between the years 2009, 2014, and 2019. The overall accuracy of supervised classification images in 2009, 2014, and 2019 was 80.00 per cent, 86.63 per cent and 97.75 per cent, respectively. Based on respondents, the most significant causes of deforestation in the study area are accessibility factors, land use factors, government policy management factors, human factors, ecology and finally, population and socio-economic factors.